Medical Image Fusion Algorithm Based on Nonlinear Approximation of Contourlet Transform and Regional Features. (24th January 2017) - Huang, Hui; Feng, Xi'an; Jiang, Jionghui
Abstract : According to the pros and cons of contourlet transform and multimodality medical imaging, here we propose a novel image fusion algorithm that combines nonlinear approximation of contourlet transform with image regional features. The most important coefficient bands of the contourlet sparse matrix are retained by nonlinear approximation. Low-frequency and high-frequency regional features are also elaborated to fuse medical images. The results strongly suggested that the proposed algorithm could improve the visual effects of medical image fusion and image quality, image denoising, and enhancement.